Norwegian Secondary School Teachers’ Reflections on Models for Physical Activity During Schooltime: A Longitudinal Intervention Study - Lomsdal, Sondre Arntzen; Lyngstad, Idar Kristian; Lagestad, Pål Arild (Frontiers in Education, 2022)
To prevent the negative trend regarding youths’ physical activity (PA) level, schools have been promoted as an appropriate arena for facilitating increased PA among youths. This study focuses on Norwegian secondary school teachers’ perceptions of models for PA during schooltime, by interviews before, during and after a PA intervention, where various PA models are implemented in a secondary school. An important finding is that implementation of PA at school must consider the complexity of the teacher’s practice, the diversity of students, and the need for flexibility among teachers in their daily practice. Our study show that facilitating PA in secondary school by using several methods, is experienced as the most preferable approach by the teachers, and this supports the idea of a whole-school approach. Future research should focus on interventions where teachers gain experience with all the models aimed at implementing PA in school.